Pilgrims and promoters at Beauraing and Banneux: The evolution from apparition to pilgrimage sites, 1932–1949 - Osselaer, Tine van (Trajecta, 2025)
This article studies the development of the pilgrimage sites in Beauraing and Banneux, the two original locations of a wave of apparitions that swept across Belgium in the 1930s. Studying the initiatives of the promoters of the sites and the responses of the devotees, the article traces their evolution from apparition to pilgrimage sites. While the initial response to the enthusiastic devotees was one of controlling and monitoring (as the prime focus was on the visionaries), in a later phase, the pilgrims’ experience gained more importance. The promoters catered to the pilgrims, as they knew the importance of the ‘sensus fidelium’ in the evaluation of Marian apparitions and the positive impression miraculous cures would make. Improving the sites (e.g. establishing hospitals for the sick) and the practical organization of the pilgrimages allowed the sick and other sufferers to visit a site where divine intervention had proven possible and might happen again. Rather than solely studying the material evolution and the perspective of the promotors, this article thus also focuses on how the sites were meant to be experienced and were experienced by the devotees. We will see how the faithful adopted the sites beyond the contours set by the promoters and thus how Beauraing and Banneux became sites where all Marian devotees could find consolation and comfort. They were no longer merely places where visionary children had once been singled out.